2000
DOI: 10.1128/cdli.7.6.940-944.2000
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Quantification of Antibodies to Newcastle Disease Virus in Ostrich and Rhea Sera Using a Liquid Phase Blocking Enzyme-Linked Immunosorbent Assay

Abstract: A liquid phase blocking ELISA (LPB-ELISA) was adapted for the detection and quantification of antibodies to Newcastle disease virus. Sera from vaccinated and unvaccinated commercial flocks of ostriches (Struthio camelus) and rheas (Rhea americana) were tested. The purified and nonpurified virus used as the antigen and the capture and detector antibodies were prepared and standardized for this purpose. The hemagglutinationinhibition (HI) test was regarded as the reference method. The cutoff point for the LPB-EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The sensitivity, specificity, and predictive accuracy of the B-ELISA and the HI test relative to the VN test were similar. Moro et al [18] reported that a liquid phase B-ELISA and HI test with heat and kaolin treatment showed good agreement. False positive reaction in the HI test might arise from ostrich species.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The sensitivity, specificity, and predictive accuracy of the B-ELISA and the HI test relative to the VN test were similar. Moro et al [18] reported that a liquid phase B-ELISA and HI test with heat and kaolin treatment showed good agreement. False positive reaction in the HI test might arise from ostrich species.…”
mentioning
confidence: 98%
“…Each test serum sample was treated at 56°C for 30 min and then incubated with kaolin at 37°C for 30 min to extract nonspecific inhibitors [18,23]. Subsequently, the treated sera were incubated with 10% chicken red blood cells at room temperature for 10 min [5].…”
mentioning
confidence: 99%
“…When tested by HI assay or ELISA, the antibodies titers after treatment with kaolin did not vary either (Sousa et al 2000).…”
Section: Virus Reviews and Research 13 2008mentioning
confidence: 99%
“…However, HI test tends to give false positive results in serum samples of some species including ostriches, due to the presence of nonspecific hemagglutination inhibitors (Willians et al 1997, Alexander 1997, Koch et al 1998, Sousa et al 2000. According to the OIE (2004), serum samples can be incubated with 10% chicken red blood cells (RBCs) suspension at room temperature, for 10 min, to eliminate these agents.…”
Section: Virus Reviews and Research 13 2008mentioning
confidence: 99%
See 1 more Smart Citation